Within-Subject Comparison of [11C]-( + )-PHNO and [11C]raclopride Sensitivity to Acute Amphetamine Challenge in Healthy Humans - Shotbolt, Paul; Tziortzi, Andri C; Searle, Graham E; Colasanti, Alessandro; van der Aart, Jasper; Abanades, Sergio; Plisson, Christophe; Miller, Sam R; Huiban, Mickael; Beaver, John D; Gunn, Roger N; Laruelle, Marc; et al. (Journal of cerebral blood flow and metabolism, 2012)
[11C]PHNO is a D2/D3 agonist positron emission tomography radiotracer, with higher in vivo affinity for D3 than for D2 receptors. As [11C]-( + )-PHNO is an agonist, its in vivo binding is expected to be more affected by acute fluctuations in synaptic dopamine than that of antagonist radiotracers such as [11C]raclopride. In this study, the authors compared the effects of an oral dose of the dopamine releaser amphetamine (0.3 mg/kg) on in vivo binding of [11C]-( + )-PHNO and [11C]raclopride in healthy subjects, using a within-subjects, counterbalanced, open-label design. In the dorsal striatum, where the density of D3 receptors is negligible and both tracers predominantly bind to D2 receptors, the reduction of [11C]-( + )-PHNO binding potential (BPND) was 1.5 times larger than that of [11C]raclopride. The gain in sensitivity associated with the agonist [11C]-( + )-PHNO implies that ~65% of D2 receptors are in the high-affinity state in vivo. In extrastriatal regions, where [11C]-( + )-PHNO predominantly binds to D3 receptors, the amphetamine effect on [11C]-( + )-PHNO BPND was even larger, consistent with the higher affinity of dopamine for D3. This study indicates that [11C]- ( + )-PHNO is superior to [11C]raclopride for studying acute fluctuations in synaptic dopamine in the human striatum. [11C]-( + )-PHNO also enables measurement of synaptic dopamine in D3 regions.